Nannie Helen Burroughs : A Documentary Portrait of an Early Civil Rights Pioneer, 1900-1959 - Burroughs, Nannie Helen, 1879-1961 (Book collections on Project MUSE., 2019)
"This would be the first comprehensive intellectual history of Burroughs and a compendium of her most important and influential work. As a force in the civil rights movement of the early 20th century, Burroughs and her work has largely been relegated to inclusion in larger narratives of those events. Rarely has her life and work been considered on its own, and as Graves demonstrates, Burroughs was quite prescient on many issues confronting the African American community today."